Optimizing agroforestry in Tanjung Beringin Village increases farmers’ income through effective planting patterns and crop combinations: - - Basuki, Rahmad; Rahim, Supli Effendi; Helida, Asvic (Indonesian Soil Science Society of South Sumatra in Collaboration With Soil Science Department, Sriwijaya University, 2025)
Agroforestry is a land use system that integrates agricultural and forestry crops in the same area, providing a balance between production and conservation for social, economic and ecological benefits. Farmers at the Lembah Bukit Besak Village Forest Institute, Tanjung Beringin Village, South Merapi District, have implemented this system. The research aims to identify planting patterns and composition of agroforestry plants, evaluate the most optimal plants to increase income, and formulate strategies for adopting the best planting patterns. This study used a census method to collect data from 75 farmers in the Rimba Bukit Besar Village Institution group. After conducting a sampling method using a purposive stratified random sampling method, 24 farmer respondents were obtained. The research results show two main planting patterns: a random mixture, applied by 66.67% of farmers, and tree along border pattern, applied by 33.33%. The most profitable crops are coffee, rubber, jengkol, durian and eggplant (Solanum melongena). The